2015
DOI: 10.1007/s10397-015-0893-5
|View full text |Cite
|
Sign up to set email alerts
|

Pictorial blood loss assessment chart for quantification of menstrual blood loss: a systematic review

Abstract: To evaluate the diagnostic accuracy of pictorial blood loss assessment chart (PBLAC) compared to objective measurements of menstrual blood loss (MBL), a systematic search of MEDLINE, EMBASE, Cumulative Index to Nursing & Allied Health Literature (CINAHL), Web of Science, and EBM Reviews-Cochrane Central Register of Controlled Trials from inception until September 30, 2014 was performed. Terms referring to Bpictorial blood loss assessment chart,^Bmenstrual blood loss evaluation,^and Balkaline hematin^were used.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 32 publications
0
15
0
1
Order By: Relevance
“…The primary outcome was menstrual blood loss that was assessed with pictorial blood loss assessment chart (PBAC) (15,16). The PBAC score was calculated by assigning a score of 1, 5, or 20, respectively, to a lightly, moderately, or fully soiled sanitary pad, and a score of 1 or 5, respectively, for the passage of small or large clots.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…The primary outcome was menstrual blood loss that was assessed with pictorial blood loss assessment chart (PBAC) (15,16). The PBAC score was calculated by assigning a score of 1, 5, or 20, respectively, to a lightly, moderately, or fully soiled sanitary pad, and a score of 1 or 5, respectively, for the passage of small or large clots.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…In the past, tyramine and choline were responsible for controlling the bleeding by the plant. Todays, new researches have shown that other substances that are not fully recognized may be responsible for such an effect [25][26][27][28][29][30][31][32][33][34][35][36][37][38]. Anyway, the contractile and hemostatic nature of this drug cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…If the score is more than 100, it indicates uterine bleeding is more than 80 cc. The accuracy of this test has been reported differently in different studies but is still the most applicable method for measuring the amount of menstrual blood loss [34]. In addition, the Persian version of the Menorrhagia Questionnaire (MQ) was used to assess the quality of life.…”
Section: Measurementsmentioning
confidence: 99%
“…28 However, its sensitivity and specificity vary widely. 29 For a qualitative assessment, several menstrual bleeding-specific questionnaires that incorporate quality-of-life assessment have been used. 30,31 However, a standardized and validated questionnaire is needed to attenuate variability in outcomes and to increase generalizability.…”
Section: How To Assess Hmb In Clinical and Research Settingsmentioning
confidence: 99%